Site-Directed Mutagenesis Study Revealed Three Important Residues in Hc-DAF-22, a Key Enzyme Regulating Diapause of Haemonchus contortus - Huang, Yan; Zheng, Xiuping; Zhang, Hongli; Ding, Haojie; Guo, Xiaolu; Yang, Yi; Chen, Xueqiu; Zhou, Qianjin; Du, Aifang (Frontiers in Microbiology, 2017)
Haemonchus contortus (H. contortus) is one of the most important parasites of small ruminants, especially goats and sheep. The complex life cycle of this nematode is a main obstacle for the control and prevention of haemonchosis. So far, a special form of arrested development called diapause different from the dauer stage in Caenorhabditis elegans (C. elegans) has been found in many parasitic nematodes. In our previous study, we have characterized a novel gene Hc-daf-22 from H. contortus sharing high homology with Ce-daf-22 and functional analysis showed this gene has similar biological function with Ce-daf-22. In this study, Hc-daf-22 mutants were constructed using site-directed mutagenesis, and carried out rescue experiments, RNA interference (RNAi) experiments and in vitro enzyme activity analysis with the mutants to further explore the precise function site of Hc-DAF-22. The results showed that Hc-daf-22 mutants could be expressed in the rescued ok693 worms and the expression positions were mainly in the intestine which was identical with that of Hc-daf-22 rescued worms. Through lipid staining we found that Hc-daf-22 could rescue daf-22 mutant (ok693) from the fatty acid metabolism deficiency while Hc-daf-22 mutants failed. Brood size, body length and life span analysis in both rescue and RNAi experiments elucidated that Hc-daf-22 resembled Ce-daf-22 in effecting the development and capacity of C. elegans and mutants impaired the function of Hc-daf-22. Together with the protease activity assay, this research revealed three important active resides 84C/299H/349H in Hc-DAF-22 by site-directed mutagenesis.